2020
DOI: 10.3928/01477447-20191212-05
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Kager's Triangle in Detecting Acute Achilles Tendon Ruptures

Abstract: The Achilles tendon is a common site of anatomical injury among athletes and those participating in recreational sporting activities. Acute Achilles tendon ruptures are often misdiagnosed as a sprained ankle and are more common in the male population. Mechanism of injury is often a noncontact injury, resulting from sudden forced plantar flexion or violent dorsiflexion in a plantar flexed foot. Delays in diagnosis and treatment may complicate the clinical outcome. Because findings may be subtle on history and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…26 Several studies and case reports have previously suggested that Kager’s fat pad sign may be helpful in diagnosing ATR. 15,21,24 Cetti and Andersen 15 reported the sensitivity of Kager’s fat pad sign as 100% and its specificity as 98.3%, for the diagnosis of ATR. These diagnostic values are much higher than those we observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Several studies and case reports have previously suggested that Kager’s fat pad sign may be helpful in diagnosing ATR. 15,21,24 Cetti and Andersen 15 reported the sensitivity of Kager’s fat pad sign as 100% and its specificity as 98.3%, for the diagnosis of ATR. These diagnostic values are much higher than those we observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A positive Kager’s fat pad sign is defined as the sharp edges of Kager’s triangle disappearing or becoming indistinct and obscured, or the triangle becoming more radio dense and covered by a network-like shadow (Figure 1). 15,24…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the findings of the history and physical examination may be ambiguous (3), radiographic imaging plays a key role in diagnosis in emergency situations. Although Kager's sign has been defined as a radiographic sign of Achilles tendon rupture, its diagnostic efficacy has not been well studied and has not been frequently used in clinical practice (4). Magnetic resonance imaging (MRI) is the gold standard imaging method in the diagnosis of tendinopathies ( 5), however, it has disadvantages such as being impractical in emergency situations, not being accessible in all facilities, and being expensive.…”
Section: Introductionmentioning
confidence: 99%